Pengaruh Efektivitas Kerja Bhabinkamtibnas Terhadap Kinerja Kepala Desa Dalam Pengelolaan Dana Desa di Kecamatan Sembawa Kabupaten Banyuasin - Nanda Revita; Marita Pratisila; Imam Suroso; Indah Mawarni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
The aims of this study were to determine the effects of Bhabinkamtibnas work effectiveness on performance of village head in managing village funds at Sembawa district Banyuasin. This research was associative quantitative. The data collection method used was the purposive sampling. Respondents in this study were all employees of the village office of the Sembawa district of i.e. 121 employees. The data collection tool used in this study was a questionnaire. The data were analysed using pearson product moment correlation. The conclusions that can be drawn from this study were Bhabinkamtibnas work effectiveness had a positive and significant effect on performance of village head in managing village funds at Sembawa district Banyuasin.